2009
DOI: 10.2337/db09-0902
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Cerebral Neovascularization in a Model of Type 2 Diabetes

Abstract: OBJECTIVEThe effect of diabetes on neovascularization varies between different organ systems. While excessive angiogenesis complicates diabetic retinopathy, impaired neovascularization contributes to coronary and peripheral complications of diabetes. However, how diabetes influences cerebral neovascularization is not clear. Our aim was to determine diabetes-mediated changes in the cerebrovasculature and its impact on the short-term outcome of cerebral ischemia.RESEARCH DESIGN AND METHODSAngiogenesis (capillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 43 publications
9
94
2
1
Order By: Relevance
“…Many studies have examined the effects of diabetes on BBB function (45) and its response to stroke. The results have been in striking agreement, showing that diabetes exacerbates the disruption of the BBB (15,38). By using the STZ model of T1D, our group and others (8,10,15) have demonstrated that diabetic mice exhibit significantly greater hemorrhage volume and extravasation of blood-borne dyes in peri-infarct cortex 1-3 days after stroke (Fig.…”
Section: Dysfunction Of the Blood-brain Barriersupporting
confidence: 69%
See 1 more Smart Citation
“…Many studies have examined the effects of diabetes on BBB function (45) and its response to stroke. The results have been in striking agreement, showing that diabetes exacerbates the disruption of the BBB (15,38). By using the STZ model of T1D, our group and others (8,10,15) have demonstrated that diabetic mice exhibit significantly greater hemorrhage volume and extravasation of blood-borne dyes in peri-infarct cortex 1-3 days after stroke (Fig.…”
Section: Dysfunction Of the Blood-brain Barriersupporting
confidence: 69%
“…2G and I). Although this finding may seem counterintuitive, a study by Li et al (38) that used laser Doppler imaging for regional estimates of cerebral blood flow also showed elevated blood flow 24 h after stroke in the GK T2D rat. In the Tennant and Brown study, administration of insulin to hyperglycemic mice immediately after stroke provided only a partial normalization of blood velocity levels (Fig.…”
Section: Effects Of Diabetes On Cerebral Blood Flow and Vascular Remomentioning
confidence: 95%
“…Li et al had confirmed that angiogenesis and arteriogenesis showed remarkable increases in the number of collaterals, the diameters of the collaterals, the number of anastomoses, and microvessel density in T2DM Goto-Kakizaki rats. 16 The experimental results revealed a significant rise in the level of vascular endothelial growth factor (VEGF) and nitrotyrosine. 24 The levels of growth factors and cytokines that were regarded as important in the development of sprouting collateral vessels from the extracranial vascular system by indirect revascularization, such as the expression of VEGF, basic fibroblast growth factor, transforming growth factorb, granulocyte colony-stimulating factor, and hepatocyte growth factor, have been proven to be elevated in many studies in MMD patients.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…We have shown that diabetes causes increased, yet dysfunctional, neovascularization in the cerebrovasculature. [30][31][32] There is increased arteriogenesis (greater number of collaterals and increased vascular tortuosity) in the pial vasculature of type 2 diabetic Goto-Kakizaki (GK) rats. 30 A follow-up study provided evidence for increased cerebral angiogenesis and arteriogenesis.…”
Section: Diabetes and Neovascularizationmentioning
confidence: 99%